Gestión administrativa de la Feterreria Becerra del periodo 2020 - Fernández Ninabanda, Silvia Gisela (2021)
This research work analyzes the management of the administrative management of the Ferretería Becerra, located in the Guaranda canton; determine what are the processes that employees maintain within their activities, what their functions are, how they develop them in each area and the results obtained from the administrative management they are carrying out, in addition to determining the work environment, knowing the type of communication they maintain , and the control that is given was the main point. To prepare it, a descriptive and qualitative type of research was used, the interview and survey technique was applied, in addition to the bibliographic review. The administrative situation within the hardware store represents a remarkable effort on the part of the owner who, without having prior knowledge of administrative management, has developed an empirical system, which has allowed him to run his company and expand it for several years, however it is necessary to improve it. Through short, medium and long-term planning, organization of processes so that workers can better develop activities and the determination of activities according to the area, follow-up through internal control. If the owner takes into account each and every one of the steps and guidelines that have been established, because he is focused on improving his interaction process with employees, a mutual benefit will be generated. In this way, greater productivity can be created within the hardware store, which will help the economic growth of the same.